2010
DOI: 10.1029/2009ja015188
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric variability due to planetary waves and tides for solar minimum conditions

Abstract: [1] Large ionospheric variability is found at low to middle latitudes when a quasi-stationary planetary wave is specified in the winter stratosphere in the National Center for Atmospheric Research thermosphere-ionosphere-mesosphere electrodynamics general circulation model for solar minimum conditions. The variability includes change of electric field/ion drift, F2 peak density and height, and the total electron content. The electric field/ion drift change is the largest near dawn in the numerical experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
351
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(379 citation statements)
references
References 44 publications
(50 reference statements)
25
351
1
2
Order By: Relevance
“…This process probably involves sources not only from changes in high-latitude inputs caused by solar-wind and IMF driving conditions, but also from planetary waves from the lower atmosphere as well as the nonlinear interaction between these processes. The planetary waves can affect the F-region ionosphere through the modification of both background winds and tides, and consequently, the E-region dynamo and F-region ionosphere (Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process probably involves sources not only from changes in high-latitude inputs caused by solar-wind and IMF driving conditions, but also from planetary waves from the lower atmosphere as well as the nonlinear interaction between these processes. The planetary waves can affect the F-region ionosphere through the modification of both background winds and tides, and consequently, the E-region dynamo and F-region ionosphere (Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…They might also be related to the lower-atmospheric planetary waves that propagate upward to the mesosphere and lower-thermosphere region causing changes in the ionosphere (López-González et al, 2009). In fact, Liu et al (2010) showed, using model simulations, that stationary planetary waves can modify semidiurnal tides which, in turn, produce changes in the neutral-wind dynamo and introduce periodicities in the ionospheric peak density and total-electron content that have the same periods as those of the planetary waves.…”
Section: Discussionmentioning
confidence: 99%
“…Global climatology of 2-, 5-, 10-and 16-day waves has been established by satellite measurements, e.g., Gu et al (2013), Moudden and Forbes (2014) for 2-day waves; Wu et al (1994) If the amplitude of the planetary waves is sufficiently large in the dynamo region, they will drive ionospheric currents and affect geomagnetic perturbations on the ground. Even if the planetary waves dissipate before they reach the dynamo region, they can still interact with tides and mean flow in the middle atmosphere, which will affect the upward propagation of tides to the dynamo region, and thus affect the ionospheric dynamo (e.g., Liu et al 2010;Chang et al 2011). Either case, the presence of the planetary waves would lead to oscillations of Sq and EEJ with periods similar to those of the waves.…”
Section: Planetary Wave Effectmentioning
confidence: 99%
“…Those tidal changes can result from changes in the mean flow (e.g., Stening et al 1997), interaction with planetary waves (e.g., Liu et al 2010;, and changes in the tidal sources (e.g., Goncharenko et al 2012). Besides, Forbes and Zhang (2012) suggested that a change in the resonance property of the atmosphere during stratospheric sudden warming events leads to a significant increase in the amplitude of semidiurnal lunar tides.…”
Section: Stratospheric Sudden Warming Effectmentioning
confidence: 99%
“…A number of observation and simulation works in literature have shown that planetary-scale waves, including atmospheric tides and various stationary and traveling planetary waves in the mesosphere and lower thermosphere (MLT), are able to impact the ionosphere/thermosphere (IT) system substantially (Laštovička, 2006;Forbes et al, 2009;Pedatella et al, 2009;Chang et al, 2010;Liu et al, 2010;England, 2012;Yue et al, 2013a;Yamazaki and Richmond, 2013;Yue and Wang, 2014;Chang et al, 2014). The planetary-scale wave signals with the same period and zonal wavenumber as those in the lower atmosphere are often observed in the IT system, which are thought to be the result of either the direct vertical propagation of the planetary-scale waves into the upper thermosphere or via the wave modulation on the neutral wind and dynamo electric fields in the ionosphere E region (Laštovička and Sauli, 1999;Pancheva et al, 2002;England et al, 2006).…”
Section: Introductionmentioning
confidence: 99%